Effect of enzyme addition on energy utilization and performance of broiler chickens fed wheat-based diet with different metabolizable energy levels - Seyed adel Moftakharzadeh; Hossein Janmohammadi; Akbar Taghizadeh; Ruhollah Kianfar; Majid Geshlog Olyayee (Acta Scientiarum. Animal Sciences, 2019)
An experiment was carried out to investigate the effect of multi-enzyme in high and low levels of metabolizable energy (13.81 and 11.51 MJ kg-1 diet) on performance and energy utilization of broilers fed wheat-soybean meal diets from 0 to 21 days of age. Result showed that birds fed diets containing 11.51 MJ kg-1 consumed significantly (p < 0.05) more feed than diets containing 13.81 MJ kg-1, whereas daily gain and feed conversion ratio improved (p < 0.05) when enzyme was added to 11.51 MJ kg-1 diet. There was significant improvement in metabolizable energy, net energy for production, organic and dry matter digestibility in 0-21 when diets supplemented with enzyme (p < 0.05). Addition of enzyme to 11.51 MJ kg-1 containing diet significantly (p < 0.05) reduced heat production of birds in 0-10 d, whereas heat production was not changed in 21 days. Supplementation of 11.51 MJ kg-1 diet with enzyme improved the efficiency of ME use for carcass energy and protein retention of broilers (p < 0.05). Generally, the results of current study demonstrated that addition of enzyme to wheat-soybean diets improved NEp of broiler chickens while MEI was not changed and it seems NEp is a more sensitive energy utilization response criterion to use in evaluating broilers response to enzyme supplementation.